History of Phases in Textbook Revisions at the 1928 Oslo Conference from the Hungarian Perspective - Albert, Gábor (International Dialogues on Education Journal, 2016)
This study is focused on phases of the textbook revision movement and textbook debates from the Oslo Conference organized by the International Committee of Historians in 1928. It is based on interviews by the contemporary Norwegian newspaper “Aftenposten” and on reports to the Hungarian Ministry of Education written by the Hungarian conference delegate, Sandor Domanovszky, one of the greatest Hungarian historians and authors of textbooks. Further, the author examines Kuno Klebelsberg’s (leader of the Hungarian Ministry of Education between 1922 and 1931) attitudes to the textbook issue. After World War I the Hungarian textbook revision movement was examined in depth by the institutions of the League of Nations, and at events of the International Committee of Historical Science (Comité International des Sciences Historiques – CISH). The textbook revision movement aimed to filter out tendentious and distorted prejudices towards other nations in history textbooks.